OPTIMALISASI PRINSIP GOOD GOVERNANCE UNTUK MENINGKATKAN PELAYANAN PUBLIK DI KABUPATEN BIREUEN - Fitri Ernalis; Taufik Jahidin; Yusrawati; Afriana; Muhammad Iqbal (LPPM Universitas Ekasakti, 2024)
The concept of good governance plays a crucial role in creating an effective, efficient, and independent local government, especially in the field of population administration. The Population and Civil Registration Office of Bireuen Regency strives to implement the principles of good governance but faces various challenges that hinder the optimization of public services. These challenges include the suboptimal performance of bureaucratic apparatus, a lack of transparency and accountability, and bureaucratic complexities that result in citizens feeling obstructed in meeting their administrative needs. Additionally, low participation from both the community and the private sector in policy-making and program evaluation creates a gap between the government, society, and private entities, often leading to policies that do not align with the expectations and needs of the people. This study aims to evaluate the implementation of the principles of good governance in the service of issuing electronic ID cards (e-KTP) at the Population and Civil Registration Office of Bireuen Regency. The method used is a qualitative approach, with analysis based on good governance principles according to the National Institute of Public Administration. The results of the study indicate that the implementation of good governance principles in public services, particularly in the issuance of e-KTP, has not been optimal. This is evident from the gap between established policies and the realities on the ground, where citizens still face various obstacles in accessing fast, transparent, and accountable services. Therefore, it is essential for the Population and Civil Registration Office to continually improve service quality, enhance community involvement, and ensure that good governance principles are consistently applied to create a better and more responsive government that meets the needs of the people.